ANALISIS STABILITAS LERENG DAN PERENCANAAN DINDING PENAHAN TANAH PADA STA 114+000 RUAS JALAN SANGATA – Sp. PERDAU KALIMANTAN TIMUR - SYEFIRA, HERIYADI (KURVA S JURNAL MAHASISWA, 2014)
The slopes are natural surface appearance due to the height difference . The height difference of two places compared with the straight distance horizontally so that would be obtained magnitude of slope ( slope) . At the place where two different ground surfaces ketinggianya , then there will be forces at work pushing so that the soil of higher social status tend to move toward the bottom. Besides the force that drives down there are also forces in the land who work hold the soil so that the position remains stable .               Based on the formulation of the problem and the results of slope stability analysis and planning of retaining wall on the activities of STA 114 + 000 Jalan Sanggata-Sp. Perdau East Kalimantan can be summarized as follows:1. The calculation of slope stability using Geoslope program obtained value of F or FOS = 2.399 which means it is by planning a slope like this are relatively stable and secure, where Values Safety Factor F or FOS = 2.399> 1.252. For Planning cantilevered retaining wall structures obtained:a. Size planning retaining wall is:- High Retaining Walls Soil = 8 meters- Width and Height leg Retaining Walls Soil = 0.8 x 4 metersb. Bolster the stability gained 2.148> 1.5 (secure)c. Scroll stability gained 5.572> 1.5 (secure)d. Stability Against Collapse of Carrying Capacity of Land gained 3.432> 3 (OK)               From the results of planning is recommended as follows:1. For the planning of retaining wall is good because a safety factor greater than 1.5 (> 1.5) and therefore its dimensions are still able to be minimized.2. It is recommended to use geotextile between the original ground surface with granular soil embankment so that the soil is not mixed.3. Soil pile must either (well graded) as proposed in the plan.